Efficacy of Vitamin C and E on the Level of Antioxidative Stress and Steroid Hormones in Albino Rats with Environmental Stress - Winda Kusuma Dewi; Faisal Fikri; Agus Purnomo; Shekhar Chhetri; Salipudin Tasil Maslamama; Muhammad Thohawi Elziyad Purnama (The Indian Veterinary Journal, 2024)
The aim of this study was to evaluate the efficacy of vitamin C and E in albino rats exposed with environmental stress on the following variables i.e. superoxide dismutase, malondialdehyde, catalase, testosterone, and cortisol level. A total of 20 albino rats were assigned into four treatment groups i.e. (C) normal saline, (T1) vitamin C and E, (T2) induced with stress, (T3) induced with stress and vitamin C and E. All groups were maintained for 4 weeks, respectively. Serum samples were collected from 5 ml of blood, respectively then evaluated using enzymol method for level of antioxidative stress and ELISA method for steroid hormone determination.In result, T3group improved significantly difference compared to T2 group in the variable of malondialdehyde, catalase, testosterone, and cortisol. Meanwhile, there was no significant difference in the superoxide dismutase level between T3 and T2groups. In conclusion, vitamin C and E had an efficacy to ameliorate albino rats condition exposed with environmental stress.